Implications of new monoclonal antibodies and the crystal structure of the TSH receptor for the treatment and management of thyroid diseases. (December 2008) - Rees Smith, Bernard; Sanders, Jane; Furmaniak, Jadwiga
Autoantibodies to the thyroid-stimulating hormone receptor (TSHR) cause the hyperthyroidism of Graves'' disease and contribute to Graves'' eye signs. Human monoclonal TSHR autoantibodies prepared from patients'' lymphocytes have important clinical applications in terms of their ability to stimulate TSHR-containing tissues. Also, TSHR monoclonal antibodies that act as antagonists may well be useful in treating Graves'' eye disease. Recently, the high-resolution (2.55 ÅÅ) crystal structure of the TSHR in complex with a monoclonal thyroid-stimulating autoantibody has been determined, and this provides key insights into how the autoantibodies interact with the receptor. Furthermore, the structure can be used in the rational design of small molecules that will disrupt receptor binding by thyroid-stimulating autoantibodies, thus providing new strategies to control TSHR activation in addition to monoclonal antibodies.